2022
DOI: 10.1002/ecy.3786
|View full text |Cite
|
Sign up to set email alerts
|

Experimental insect suppression causes loss of induced, but not constitutive, resistance in Solanum carolinense

Abstract: Spatiotemporal variation in herbivory is a major driver of intraspecific variation in plant defense. Comparatively little is known, however, about how changes in herbivory regime affect the balance of constitutive and induced resistance, which are often considered alternative defensive strategies. Here, we investigated how nearly a decade of insect herbivore suppression affected constitutive and induced resistance in horsenettle (Solanum carolinense), a widespread herbaceous perennial. We allowed replicated ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…one species has high defence and low growth, while another species has the opposite; Lind et al., 2013; Rotter & Holeski, 2018; Heckman et al., 2019) (but see Chauvin et al., 2018; Hinman et al., 2019), evidence for within‐species trade‐offs is weaker (Hahn et al., 2021; Heckman et al., 2019), yet this is more pertinent as host adaptation requires within‐species variation. However, specific plant organs can show trade‐offs related to defence and growth (Agrawal et al., 2012; Medina‐Villar et al., 2021), and there is evidence that some species can adaptively lower defence and increase growth in response to lower enemy pressure (Coverdale & Agrawal, 2022; Wolfe et al., 2004). Evolutionary changes in growth and defence because of enemy release should only benefit exotics that show strong growth–defence trade‐offs.…”
Section: Seven Contexts Can Alter the Influence Of Each Erh Factormentioning
confidence: 99%
See 1 more Smart Citation
“…one species has high defence and low growth, while another species has the opposite; Lind et al., 2013; Rotter & Holeski, 2018; Heckman et al., 2019) (but see Chauvin et al., 2018; Hinman et al., 2019), evidence for within‐species trade‐offs is weaker (Hahn et al., 2021; Heckman et al., 2019), yet this is more pertinent as host adaptation requires within‐species variation. However, specific plant organs can show trade‐offs related to defence and growth (Agrawal et al., 2012; Medina‐Villar et al., 2021), and there is evidence that some species can adaptively lower defence and increase growth in response to lower enemy pressure (Coverdale & Agrawal, 2022; Wolfe et al., 2004). Evolutionary changes in growth and defence because of enemy release should only benefit exotics that show strong growth–defence trade‐offs.…”
Section: Seven Contexts Can Alter the Influence Of Each Erh Factormentioning
confidence: 99%
“…Exotics coming from low‐resource environments likely have a lower growth–defence ratio than co‐occurring natives (Endara & Coley, 2011; Figure 3f, blue line). If they are released from enemies and have more resources available, exotic plants will evolve to invest more in growth than defence (Coverdale & Agrawal, 2022). This adaptation can happen in as little as 150 growing seasons (Wolfe et al., 2004) and underpins the well‐known evolution of increased competitive ability (EICA) hypothesis (Blossey & Notzold, 1995).…”
Section: Seven Contexts Can Alter the Influence Of Each Erh Factormentioning
confidence: 99%
“…Along with oral secretions, excreta or oviposition fluids are also known to act as chemical cues perceived by transmembrane pore proteins in Solanum (Gandhi et al, 2021). More interestingly, the plants of Solanum carolinense has shown trade-offs between constitutive and induced defenses (Kariyat et al, 2013) where the insect suppression reduced the induced resistance significantly more than the constitutive defenses (Coverdale and Agrawal, 2022). The intraspecific variation in Solanum genus also can also lead to differential chemical defense induction (Campbell et al, 2013;Calf et al, 2018;Müller et al, 2020) in herbivores with similar feeding habits.…”
Section: The Solanum Defense Phenotypementioning
confidence: 99%
“…For example, a common garden survey found that different non-native species suffered from 0% to more than 40% leaf herbivory from generalists (Agrawal & Kotanen, 2003). Variation in herbivore pressure should lead to variation in defense traits (Coverdale & Agrawal, 2022;Wan et al, 2022) and less intense and less frequent herbivory is theorized to select for allocation to induced defenses (Bixenmann et al, 2016). However, how this variation in generalist herbivore pressure affects any potential tradeoffs in constitutivevs.…”
Section: Introductionmentioning
confidence: 99%